Association of genetic and psychological factors with persistent pain after cosmetic thoracic surgery - Dimova, Violeta; Loetsch, Joern; Hühne, Kathrin; Winterpacht, Andreas; Heesen, Michael; Parthum, Andreas; Weber, Peter G.; Carbon, Roman; Grießinger, Norbert; Sittl, Reinhard; Lautenbacher, Stefan (Journal of Pain Research, 2015)
The genetic control of pain has been repeatedly demonstrated in human association studies. In the present study, we assessed the relative contribution of 16 single nucleotide polymorphisms in pain-related genes, such as cathechol-O-methyl transferase gene (COMT), fatty acid amino hydrolase gene (FAAH), transient receptor potential cation channel, subfamily V, member 1 gene (TRPV1), and ?-opioid receptor gene (OPRD1), for postsurgical pain chronification. Ninety preoperatively pain-free male patients were assigned to good or poor outcome groups according to their intensity or disability score assessed at 1 week, 3 months, 6 months, and 1 year after funnel chest correction. The genetic effects were compared with those of two psychological predictors, the attentional bias toward positive words (dot-probe task) and the self-reported pain vigilance (Pain Vigilance and Awareness Questionnaire [PVAQ]), which were already shown to be the best predictors for pain intensity and disability at 6 months after surgery in the same sample, respectively. Cox regression analyses revealed no significant effects of any of the genetic predictors up to the end point of survival time at 1 year after surgery. Adding the genetics to the prediction by the attentional bias to positive words for pain intensity and the PVAQ for pain disability, again no significant additional explanation could be gained by the genetic predictors. In contrast, the preoperative PVAQ score was also, in the present enlarged sample, a meaningful predictor for lasting pain disability after surgery. Effect size measures suggested some genetic variables, for example, the polymorphism rs1800587G>A in the interleukin 1 alpha gene (IL1A) and the COMT haplotype rs4646312T>C/rs165722T>C/rs6269A>G/rs4633T>C/rs4818C>G/rs4680A>G, as possible relevant modulators of long-term postsurgical pain outcome. A comparison between pathophysiologically different predictor groups appears to be helpful in identifying clinically relevant predictors of chronic pain.
EVALuna2:9288

Characterization of germ cell differentiation in the male mouse through single-cell RNA sequencing - Lukassen, Sören; Bosch, Elisabeth; Ekici, Arif Bülent; Winterpacht, Andreas (Scientific Reports, 2018)
Spermatogenesis in the mouse has been extensively studied for decades. Previous methods, such as histological staining or bulk transcriptome analysis, either lacked resolution at the single-cell level or were focused on a very narrowly defined set of factors. Here, we present the first comprehensive, unbiased single-cell transcriptomic view of mouse spermatogenesis. Our single-cell RNA-seq (scRNA-seq) data on over 2,500 cells from the mouse testis improves upon stage marker detection and validation, capturing the continuity of differentiation rather than artificially chosen stages. scRNA-seq also enables the analysis of rare cell populations masked in bulk sequencing data and reveals new insights into the regulation of sex chromosomes during spermatogenesis. Our data provide the basis for further studies in the field, for the first time providing a high-resolution reference of transcriptional processes during mouse spermatogenesis.
EVALuna2:34135

Chromatin-Remodeling Factor SPOC1 Acts as a Cellular Restriction Factor against Human Cytomegalovirus by Repressing the Major Immediate Early Promoter - Reichel, Anna; Stilp, Anne-Charlotte; Scherer, Myriam; Reuter, Nina; Lukassen, Sören; Kasmapour, Bahram; Schreiner, Sabrina; Cicin-Sain, Luka; Winterpacht, Andreas; Stamminger, Thomas (Journal of Virology, 2018)
The cellular protein SPOC1 (survival time-associated PHD [plant homeodomain] finger protein in ovarian cancer 1) acts as a regulator of chromatin structure and the DNA damage response. It binds H3K4me2/3-containing chromatin and promotes DNA condensation by recruiting corepressors such as KAP-1 and H3K9 methyltransferases. Previous studies identified SPOC1 as a restriction factor against human adenovirus (HAdV) infection that is antagonized by E1B-55K/E4-orf6-dependent proteasomal degradation. Here, we demonstrate that, in contrast to HAdV-infected cells, SPOC1 is transiently upregulated during the early phase of human cytomegalovirus (HCMV) replication. We show that the expression of immediate early protein 1 (IE1) is sufficient and necessary to induce SPOC1. Additionally, we discovered that during later stages of infection, SPOC1 is downregulated in a glycogen synthase kinase 3β (GSK-3β)-dependent manner. We provide evidence that SPOC1 overexpression severely impairs HCMV replication by repressing the initiation of viral immediate early (IE) gene expression. Consistently, we observed that SPOC1-depleted primary human fibroblasts displayed an augmented initiation of viral IE gene expression. This occurs in a multiplicity of infection (MOI)-dependent manner, a defining hallmark of intrinsic immunity. Interestingly, repression requires the presence of high SPOC1 levels at the start of infection, while later upregulation had no negative impact, suggesting distinct temporal roles of SPOC1 during the HCMV replicative cycle. Mechanistically, we observed a highly specific association of SPOC1 with the major immediate early promoter (MIEP), strongly suggesting that SPOC1 inhibits HCMV replication by MIEP binding and the subsequent recruitment of heterochromatin-building factors. Thus, our data add SPOC1 as a novel factor to the endowment of a host cell to restrict cytomegalovirus infections.IMPORTANCE Accumulating evidence indicates that during millennia of coevolution, host cells have developed a sophisticated compilation of cellular factors to restrict cytomegalovirus infections. Defining this equipment is important to understand cellular barriers against viral infection and to develop strategies to utilize these factors for antiviral approaches. So far, constituents of PML nuclear bodies and interferon gamma-inducible protein 16 (IFI16) were known to mediate intrinsic immunity against HCMV. In this study, we identify the chromatin modulator SPOC1 as a novel restriction factor against HCMV. We show that preexisting high SPOC1 protein levels mediate a silencing of HCMV gene expression via a specific association with an important viral cis-regulatory element, the major immediate early promoter. Since SPOC1 expression varies between cell types, this factor may play an important role in tissue-specific defense against HCMV.
EVALuna2:34842

Correction to: Transient receptor potential ankyrin 1 promoter methylation and peripheral pain sensitivity in Crohn’s disease (Clinical Epigenetics, (2020), 12, 1, (1), 10.1186/s13148-019-0796-9) - Gombert, Sara; Rhein, Mathias; Winterpacht, Andreas; Münster, Tino; Hillemacher, Thomas; Leffler, Andreas; Frieling, Helge (Clinical Epigenetics, 2021)
An amendment to this paper has been published and can be accessed via the original article.
CRIS-Team Scopus Importer:2021-04-09

Duchenne muscular dystrophy and malignant hyperthermia: a genetic study of the ryanodine receptor in 47 patients - Rohde, Doris; Schmitt, Heike; Winterpacht, Andreas; Münster, Tino (European Journal of Anaesthesiology, 2014)
EVALuna2:9224

Functional null mutations in the gonosomal homologue gene TBL1Y are associated with non-syndromic coarctation of the aorta - Tagariello, Andreas; Breuer, C.; Birkner, Y.; Schmidt, Stefan; Koch, Anna Maria; Cesnjevar, Robert; Rueffer, A.; Dittrich, Sven; Schneider, H.; Winterpacht, Andreas; Sticht, Heinrich; Doetsch, J.; et al. (Current Molecular Medicine, 2012)
In patients with congenital heart defects, chromosomal anomalies are 100 times more frequent than in control subjects. Coarctation of the aorta can be detected in 15-20% of patients with Ullrich-Turner syndrome. By extensively reviewing literature involving breakpoint analysis of gonosomal deletions in Ullrich- Turner syndrome patients with and without coarctation of the aorta, we identified several gonosomal homolgous gene pairs of interest. Four of these homologous gene pairs were investigated by standard DNA sequencing in a cohort of 83 patients with non-syndromic coarctation of the aorta. Subsequently stability of mutant RNA and protein was analyzed to verify functional relevance of detected mutations. We identified two unreported missense mutations in Exon 8 (p.D69H) and 9 (p.R176W) of TBL1Y. Bioinformatic analysis and 3D modelling predicted that both mutations lead to TBL1Y loss of function. In RT-PCR and Western blot analyses of HEK293 cells transfected with a vector carrying the full-length TBL1Y (wild-type and mutant), we documented the predicted protein instability by showing protein decay for both mutant proteins. TBL1Y is similar to its gonosomal homologue, TBL1X, and its autosomal homologue, TBLR1, on chromosome 3. Both genes are part of co-repressor machineries and required for transcriptional activation by transcription factors that involve CtBP1/2, which contributes to Notch signaling. Several studies have shown that Notch signalling is important for proper development of the left ventricular outflow tract. Our findings suggest that TBL1Y is involved in the genesis of non-syndromic coarctation of the aorta.
EVALuna2:9136

Inherited pain: sodium channel Nav1.7 A1632T mutation causes erythromelalgia due to a shift of fast inactivation - Eberhardt, Mirjam; Nakajima, Julika; Klinger, Alexandra; Neacsu, Cristian; Hühne, Kathrin; o' Reilly, Andrias; Kist, Andreas; Lampe, Anne K.; Fischer, Kerstin; Gibson, Jane; Nau, Carla; Winterpacht, Andreas; et al. (Journal of Biological Chemistry, 2014)
Inherited erythromelalgia (IEM) causes debilitating episodic neuropathic pain characterized by burning in the extremities. Inherited "paroxysmal extreme pain disorder" (PEPD) differs in its clinical picture and affects proximal body areas like the rectal, ocular, or jaw regions. Both pain syndromes have been linked to mutations in the voltage-gated sodium channel Nav1.7. Electrophysiological characterization shows that IEM-causing mutations generally enhance activation, whereas mutations leading to PEPD alter fast inactivation. Previously, an A1632E mutation of a patient with overlapping symptoms of IEM and PEPD was reported (Estacion, M., Dib-Hajj, S. D., Benke, P. J., Te Morsche, R. H., Eastman, E. M., Macala, L. J., Drenth, J. P., and Waxman, S. G. (2008) NaV1.7 Gain-of-function mutations as a continuum. A1632E displays physiological changes associated with erythromelalgia and paroxysmal extreme pain disorder mutations and produces symptoms of both disorders. J. Neurosci. 28, 11079-11088), displaying a shift of both activation and fast inactivation. Here, we characterize a new mutation of Nav1.7, A1632T, found in a patient suffering from IEM. Although transfection of A1632T in sensory neurons resulted in hyperexcitability and spontaneous firing of dorsal root ganglia (DRG) neurons, whole-cell patch clamp of transfected HEK cells revealed that Nav1.7 activation was unaltered by the A1632T mutation but that steady-state fast inactivation was shifted to more depolarized potentials. This is a characteristic normally attributed to PEPD-causing mutations. In contrast to the IEM/PEPD crossover mutation A1632E, A1632T failed to slow current decay (i.e. open-state inactivation) and did not increase resurgent currents, which have been suggested to contribute to high-frequency firing in physiological and pathological conditions. Reduced fast inactivation without increased resurgent currents induces symptoms of IEM, not PEPD, in the new Nav1.7 mutation, A1632T. Therefore, persistent and resurgent currents are likely to determine whether a mutation in Nav1.7 leads to IEM or PEPD.
EVALuna2:2419

Investigating PHF13 induced infertility through single cell transcriptomics and non-vertebrate model organisms - Bosch, Elisabeth; Lukassen, S.; Gregor, Anne; Ekici, Arif Bülent; Zweier, Christiane; Winterpacht, Andreas (EUROPEAN JOURNAL OF HUMAN GENETICS, 2020)
CRIS-Team WoS Importer:2021-01-22

Manifestation of epilepsy in a patient with EED-related overgrowth (Cohen-Gibson syndrome) - Hetzelt, Katalin; Winterholler, Martin; Kerling, Frank; Rauch, Christophe; Ekici, Arif Bülent; Winterpacht, Andreas; Vasileiou, Georgia; Uebe, Steffen; Thiel, Christian; Kraus, Cornelia; Reis, André; Zweier, Christiane (American Journal of Medical Genetics Part A, 2021)
Cohen-Gibson syndrome is a rare genetic disorder, characterized by fetal or early childhood overgrowth and mild to severe intellectual disability. It is caused by heterozygous aberrations in EED, which encodes an evolutionary conserved polycomb group (PcG) protein that forms the polycomb repressive complex-2 (PRC2) together with EZH2, SUZ12, and RBBP7/4. In total, 11 affected individuals with heterozygous pathogenic variants in EED were reported, so far. All variants affect a few key residues within the EED WD40 repeat domain. By trio exome sequencing, we identified the heterozygous missense variant c.581A > G, p.(Asn194Ser) in exon 6 of the EED-gene in an individual with moderate intellectual disability, overgrowth, and epilepsy. The same pathogenic variant was detected in 2 of the 11 previously reported cases. Epilepsy, however, was only diagnosed in one other individual with Cohen-Gibson syndrome before. Our findings further confirm that the WD40 repeat domain represents a mutational hotspot; they also expand the clinical spectrum of Cohen-Gibson syndrome and highlight the clinical variability even in individuals with the same pathogenic variant. Furthermore, they indicate a possible association between Cohen-Gibson syndrome and epilepsy.
CRIS-Team WoS Importer:2021-09-24

Pain relief in a neuropathy patient by lacosamide: Proof of principle of clinical translation from patient-specific iPS cell-derived nociceptors - Namer, Barbara; Schmidt, Diana; Eberhardt, Esther; Maroni, Michele; Dorfmeister, Eva; Kleggetveit, Inge Petter; Kaluza, Luisa; Meents, Jannis; Gerlach, Aaron; Lin, Zhixin; Winterpacht, Andreas; Dragicevic, Elena; et al. (EBioMedicine, 2018)
BACKGROUND: Small fiber neuropathy (SFN) is a severe and disabling chronic pain syndrome with no causal and limited symptomatic treatment options. Mechanistically based individual treatment is not available. We report an in-vitro predicted individualized treatment success in one therapy-refractory Caucasian patient suffering from SFN for over ten years. METHODS: Intrinsic excitability of human induced pluripotent stem cell (iPSC) derived nociceptors from this patient and respective controls were recorded on multi-electrode (MEA) arrays, in the presence and absence of lacosamide. The patient's pain ratings were assessed by a visual analogue scale (10: worst pain, 0: no pain) and treatment effect was objectified by microneurography recordings of the patient's single nerve C-fibers. FINDINGS: We identified patient-specific changes in iPSC-derived nociceptor excitability in MEA recordings, which were reverted by the FDA-approved compound lacosamide in vitro. Using this drug for individualized treatment of this patient, the patient's pain ratings decreased from 7.5 to 1.5. Consistent with the pain relief reported by the patient, microneurography recordings of the patient's single nerve fibers mirrored a reduced spontaneous nociceptor (C-fiber) activity in the patient during lacosamide treatment. Microneurography recordings yielded an objective measurement of altered peripheral nociceptor activity following treatment. INTERPRETATION: Thus, we are here presenting one example of successful patient specific precision medicine using iPSC technology and individualized therapeutic treatment based on patient-derived sensory neurons.
EVALuna2:35119

Single-cell RNA sequencing of adult mouse testes - Lukassen, Sören; Bosch, Elisabeth; Ekici, Arif Bülent; Winterpacht, Andreas (Scientific Data, 2018)
Spermatogenesis is an efficient and complex system of continuous cell differentiation. Previous studies investigating the transcriptomes of different cell populations in the testis relied either on sorting cells, cell depletion, or juvenile animals where not all stages of spermatogenesis have been completed. We present single-cell RNA sequencing (scRNA-Seq) data of 2,500 cells from the testes of two 8-week-old C57Bl/6J mice. Our dataset includes all spermatogenic stages from preleptotene to condensing spermatids as well as individual spermatogonia, Sertoli and Leydig cells. The data capture the full continuity of the meiotic and postmeiotic stages of spermatogenesis, and is thus ideally suited for marker discovery, network inference and similar analyses for which temporal ordering of differentiation processes can be exploited. Furthermore, it can serve as a reference for future studies involving single-cell RNA-Seq in mice where spermatogenesis is perturbed.
EVALuna2:34826

The missing link: ARID1B non-truncating variants causing Coffin-Siris syndrome due to protein aggregation - Bosch, Elisabeth; Güse, Esther; Kirchner, Philipp; Winterpacht, Andreas; Walther, Mona; Alders, Marielle; Kerkhof, Jennifer; Ekici, Arif Bülent; Sticht, Heinrich; Sadikovic, Bekim; Reis, André; Vasileiou, Georgia (Human genetics, 2024)
ARID1B is the most frequently mutated gene in Coffin-Siris syndrome (CSS). To date, the vast majority of causative variants reported in ARID1B are truncating, leading to nonsense-mediated mRNA decay. In the absence of experimental data, only few ARID1B amino acid substitutions have been classified as pathogenic, mainly based on clinical data and their de novo occurrence, while most others are currently interpreted as variants of unknown significance. The present study substantiates the pathogenesis of ARID1B non-truncating/NMD-escaping variants located in the SMARCA4-interacting EHD2 and DNA-binding ARID domains. Overexpression assays in cell lines revealed that the majority of EHD2 variants lead to protein misfolding and formation of cytoplasmic aggresomes surrounded by vimentin cage-like structures and co-localizing with the microtubule organisation center. ARID domain variants exhibited not only aggresomes, but also nuclear aggregates, demonstrating robust pathological effects. Protein levels were not compromised, as shown by quantitative western blot analysis. In silico structural analysis predicted the exposure of amylogenic segments in both domains due to the nearby variants, likely causing this aggregation. Genome-wide transcriptome and methylation analysis in affected individuals revealed expression and methylome patterns consistent with those of the pathogenic haploinsufficiency ARID1B alterations in CSS cases. These results further support pathogenicity and indicate two approaches for disambiguation of such variants in everyday practice. The few affected individuals harbouring EHD2 non-truncating variants described to date exhibit mild CSS clinical traits. In summary, this study paves the way for the re-evaluation of previously unclear ARID1B non-truncating variants and opens a new era in CSS genetic diagnosis.
CRIS-Team Scopus Importer:2024-07-26

Transient receptor potential ankyrin 1 promoter methylation and peripheral pain sensitivity in Crohn's disease - Gombert, Sara; Rhein, Mathias; Winterpacht, Andreas; Münster, Tino; Hillemacher, Thomas; Leffler, Andreas; Frieling, Helge (Clinical Epigenetics, 2019)
Background Crohn's disease is a chronic inflammatory disorder of the gastrointestinal tract associated with abdominal pain and diarrhea. Pain caused by Crohn's disease likely involves neurogenic inflammation which seems to involve the ion channel transient receptor potential ankyrin 1 (TRPA1). Since the promoter methylation of TRPA1 was shown to influence pain sensitivity, we asked if the expression of TRPA1 is dysregulated in patients suffering from Crohn's disease. The methylation rates of CpG dinucleotides in the TRPA1 promoter region were determined from DNA derived from whole blood samples of Crohn patients and healthy participants. Quantitative sensory testing was used to examine pain sensitivities. Results Pressure pain thresholds were lower in Crohn patients as compared to healthy participants, and they were also lower in females than in males. They correlated inversely with the methylation rate at the CpG - 628 site of the TRPA1 promoter. This effect was more pronounced in female compared to male Crohn patients. Similar results were found for mechanical pain thresholds. Furthermore, age-dependent effects were detected. Whereas the CpG - 628 methylation rate declined with age in healthy participants, the methylation rate in Crohn patients increased. Pressure pain thresholds increased with age in both cohorts. Conclusions The TRPA1 promoter methylation appears to be dysregulated in patients suffering from Crohn's disease, and this effect is most obvious when taking gender and age into account. As TRPA1 is regarded to be involved in pain caused by neurogenic inflammation, its aberrant expression may contribute to typical symptoms of Crohn's disease.
CRIS-Team WoS Importer:2020-01-10